Towards collaborative optimisation in a shared-logistics environment for pickup and delivery operations - Curtois, Timothy; Laesanklang, Wasakorn; Landa-Silva, Dario; Mesgarpour, Mohammad; Qu, Yi (Scitepress, 2017)
This paper gives an overview of research work in progress within the COSLE (Collaborative Optimisation in a Shared Logistics Environment) project between the University of Nottingham and Microlise Ltd. This is an R&D project that seeks to develop optimisation technology to enable more efficient collaboration in transportation, particularly real-world operational environments involving pickup and delivery problems. The overall aim of the project is to integrate various optimisation techniques into a framework that facilitates collaboration in a shared freight transport logistics environment with the overall goal of reducing empty mileage.